Pengaruh Disiplin Kerja, Kompensasi, dan Motivasi Kerja Terhadap Kinerja Karyawan pada CV. Bangkit Jaya Semarang - Yashinta Mona Amalia; Lie Liana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze and determine the influence of work discipline, compensation and work motivation on employee performance. This research uses quantitative methods. The research population was all CV employees. Bangkit Jaya Semarang numbered 90 people. The data collection method uses a questionnaire distributed to respondents in the form of a Google form. The results of data processing are in the form of respondent descriptions, variable descriptions, validity test results, reliability test results, F test results, coefficient of determination test results (R2) and hypothesis test results. The regression results in this study show that work discipline has a positive effect on employee performance, compensation has no effect on employee performance, and work motivation has a positive effect on employee performance.